Karakteristik Anak Bawah Lima Tahun (Balita) yang Mengalami Stunting di Kelurahan Donan Kabupaten Cilacap Tahun 2019 - Sujianti Sujianti; Rusmini Rusmini (KOLONI, 2023)
Stunting (short) is a linear growth disorder caused by malnutrition of chronic substance intake or chronic or recurrent infectious diseases as indicated by the Z-score of height according to age (TB / U) less than -2 standard deviation (SD). Stunting in infants has a factor that consists of the age of the child, birth weight, age group, gender, history of basic immunization, history of infectious diseases, history of exclusive breastfeeding and the first age of MP-ASI administration. Research Objective: To determine the characteristics of children under five who experience stunting in the Donan Village, Cilacap Regency. Research Method: The method used is descriptive with cross sectional approach. The sampling technique used was cluster random sampling with a number of 100 toddlers. The analysis in this study uses univariate analysis. Results: Based on the results of the study as many as 85% of stunting toddlers aged 24-59 months, 56% of stunting toddlers of male sex, 48% of stunting toddlers with sufficient birth weight (2500-400 grams), 100% of stunting toddlers get complete basic immunization , 78% of stunting toddlers get exclusive breastfeeding, 22% of stunting toddlers who have received MP-ASI <6 months, 100% of stunting toddlers have experienced infectious diseases (ARI and Diarrhea). Conclusion: characteristics of children under five who experience stunting are aged 24-59 months, male sex, adequate birth weight, complete basic immunization, exclusive breastfeeding, MP-ASI aged ≥6 months, and having experienced infectious diseases. Keywords: Toddler, Characteristics, Stunting